Philippines Economic Update, December 2020 : Building a Resilient Recovery - World Bank (World Bank, Washington, DC, 2020)
The Philippine economy contracted by 10.0 percent, year-on-year, in the first three quarters of 2020, given the triple shock brought by the Coronavirus disease (COVID-19) pandemic. COVID-19 delivered a triple shock of a health crisis, strict containment measures, and a global recession of unprecedented scale. The sharp contraction in the second quarter was driven by the steep dive in private domestic demand, deep contraction in public investment activities, and the collapse of trade due to the impact of strict containment measures domestically and globally. Most of the country entered a more relaxed community quarantine in mid-August with a gradual opening of businesses and government operations. Yet, the economy further contracted in the third quarter, albeit a modest improvement from the peak of the outbreak. Moreover, the country was hit by a series of strong typhoons which may cause delay on the pace of the recovery as economic activities were affected in some areas. This report will feature disaster risk management (DRM) challenges the country faces and policy recommendations to strengthen its fiscal, physical, and social resilience. The severity of the recession can be explained, first and foremost, by the collapse in private consumption, as containment measures led to a fall in employment and incomes. Private consumption contracted by 8.2 percent, its worst performance on record. This was in large part due to a combination of factors that crippled domestic demand, including record-high unemployment, declining incomes (including remittances), movement restrictions that suppressed consumption, and a historic decline in consumer confidence. The deepest contraction was registered in the consumption of non-essential goods and services and those that were affected by the implementation of strict containment measures, while essential goods such as food registered small positive growth. In particular, the combination of travel restrictions and weak consumer confidence which weighed on demand, resulted in a collapse in domestic tourism expenditures, which make up a fifth of private consumption.